An Electrolytically Prepared Colloidal Silver Preparation Protects against Citrate-induced Toxicity in Artemia franciscana Nauplii - Cock, Ian Edwin; Whitehouse, Michael (Pharmacognosy Communications)
Introduction: Nanotechnology is promising for the development of new effective medicines. Silver nanoparticle preparations have been particularly well studied and a range of beneficial effects have been identified. Despite this, the sale of Colloidal silver (CS) preparations for therapeutic purposes has been banned by multiple regulatory authorities (including the FDA and TGA) on the basis of their perceived toxicity. This study evaluates the toxicity of electrolytically produced (CS) preparation, as well as some compounds used to produce CS by chemical synthesis. Materials and Methods: Toxicity of the CS preparation and the chemical toxins were evaluated using the Artemia nauplii toxicity assay. Additionally, the CS was tested for its protective effects against citrate and tannic acid-induced toxicity by screening combinations of CS and the toxins. Results: The CS preparation was nontoxic in the Artemia nauplii bioassay at all concentrations tested and did not induce mortality substantially above the seawater control at all concentrations ≤50 μg/mL. In contrast, citrate and tannic acid were strongly toxic, with LC50 values of 11.6 and 26.8 μg/mL respectively. Interestingly, co-incubation of varying concentrations of the CS preparation with 30 μg/mL of citrate resulted in protection against toxicity, with 50 μg/mL CS inhibiting ~65% of citrate-induced toxicity. In contrast, the CS preparation had no apparent effects on tannic acid-induced toxicity. Conclusion: The CS preparation tested in our study was nontoxic at all concentrations tested. Furthermore, the CS mitigated the toxic effects of citrate, but had no apparent effect on tannic acid-induced toxicity. Further studies are required to verify these findings in other toxicity models and to study the protective molecular mechanisms.
Keywords: Silver nanoparticles; Colloidal silver; Citric acid toxicity; Tannic acid; Brine shrimp toxicity; Protection against toxicity.